(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Rheumatic heart disease (RHD) represents one of the most significant yet preventable causes of cardiovascular morbidity and mortality worldwide. It develops as a chronic sequela of acute rheumatic fever (ARF), an autoimmune inflammatory reaction triggered by infection with Group A beta-hemolytic Streptococcus (GAS).